2013
DOI: 10.1096/fj.12-224006
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal protein turnover and anabolic resistance to exercise in sarcopenic obesity

Abstract: Obesity may impair protein synthesis rates and cause anabolic resistance to growth factors, hormones, and exercise, ultimately affecting skeletal muscle mass and function. To better understand muscle wasting and anabolic resistance with obesity, we assessed protein 24-h fractional synthesis rates (24-h FSRs) in selected hind-limb muscles of sedentary and resistance-exercised lean and obese Zucker rats. Despite atrophied hind-limb muscles (-28% vs. lean rats), 24-h FSRs of mixed proteins were significantly high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
76
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 78 publications
(85 citation statements)
references
References 78 publications
7
76
0
2
Order By: Relevance
“…Consistent with the current finding that skeletal muscle from obese, T2D humans exhibit hyperactive mTORC1 signaling, our laboratory (18,19) and others (53,64,72,73) have reported similar findings in skeletal muscle from obese or insulin-resistant mouse models. Similarly, findings have been reported in adipocytes from lean vs. obese individuals (55).…”
Section: R859supporting
confidence: 90%
“…Consistent with the current finding that skeletal muscle from obese, T2D humans exhibit hyperactive mTORC1 signaling, our laboratory (18,19) and others (53,64,72,73) have reported similar findings in skeletal muscle from obese or insulin-resistant mouse models. Similarly, findings have been reported in adipocytes from lean vs. obese individuals (55).…”
Section: R859supporting
confidence: 90%
“…However, in the absence of biopsies taken prior to initiation of the exercise training in the Labrador Retrievers, it is hard to make this determination. Although there is evidence from rodents that weight gain does not selectively change the synthesis rates of protein fractions (16), it is unknown whether this is true in dogs.…”
Section: Discussionmentioning
confidence: 99%
“…Longer periods of assessment are limited by the need to maintain a constant infusion of isotopes, thus restricting freeliving conditions. To address these limitations, we (4,5,13,14,19,22) and others (2,6,16,26) have employed stable isotope techniques that use deuterium oxide ( 2 H 2 O). By providing 2 H 2 O in the drinking water of humans (19,22) or rodents (4,5,13,14), we have assessed cumulative protein synthesis over the period of weeks, rather than hours.…”
mentioning
confidence: 99%
“…[22] In addition, insulin resistance may contribute to the muscle loss in diabetes, by inactivating the mammalian target of rapamycin (mTOR) pathway and stimulating autophagy. [23,24] A recent experimental study by Nilsson et al [25] showed that level of the domain-containing mTOR-interacting protein (DEPTOR), an endogenous mTOR inhibitor, was critical in the regulation of protein turnover in sarcopenic obese rats. Not only skeletal muscle size and mass reduced, bioenergy systems of the body including mitochondrial function may be also altered in these patients.…”
Section: Discussionmentioning
confidence: 99%